Vigor and Viability Testing of Rice (Oryza sativa L.) Local Mutant Germplasm of Padang Pariaman through Gamma Irradiation - Henny Puspita Sari; Irfan Suliansyah; Indra Dwipa; Dini Hervani; Winda Purnama Sari; Fatardho Zudri (Jurnal Biologi Tropis, 2023)
As a genetic resource, local rice can provide insight into the inheritance of favorable traits. Local rice varieties have naturally been tested for resistance to pests and diseases, high yields, good rice quality (including class 1 quality), and a taste that people like, but also have some disadvantages, such as long life and high plant height that easily collapses. For this reason, the characteristics of local rice varieties that have these advantages are improved using the gamma-ray induced mutation technique. Before planting in the field, it is necessary to test the vigor and viability of local rice genotypes (Oryza sativa L.) Padang Pariaman seeds first. In this study, researchers used three different rice varieties, namely: "Madang Pulau", "Putiah Papanai", and "Banang Kuniang" and gamma irradiation, with radiation doses of 0, 100, 200, 300, 400, 500, and 600 Gy. Based on the results of the study, the local rice seed varieties of Padang Pariaman Regency and the dose of gamma irradiation had a significant effect on maximum germination, while germination speed, germination capacity, vigor index, and growth uniformity were significantly affected by the dose of gamma irradiation. Gamma irradiation with doses of 400-600 Gy resulted in a more significant decrease in seed vigor and viability compared to irradiation with doses of 100-300 Gy.